2006
DOI: 10.1111/j.1442-2042.2006.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Transobturatory tension‐free composite sling for urethral support in patients with stress urinary incontinence: Favorable experience after 1 year follow up

Abstract: Objective : Symptomatic, anatomic and urodynamic results of a composite transobturatory tension-free sling with an absorbable middle part, in patients with stress urinary incontinence (SUI), were studied. Methods : A prospective study in 40 women with SUI was performed. Symptoms, urodynamics and anatomical improvements were evaluated separately. Surgery was performed with the transobturatory approach. Results : All patients had both clinically and urodynamically confirmed SUI. Clinical outcome was favorable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Ignjatovic et al . reported promising results from 40 women with 1 year follow up and demonstrated a favorable outcome at 1 year with post operative urodynamic studies showing unobstructed voiding in the majority 69 …”
Section: Newer Surgical Techniques For Suimentioning
confidence: 99%
See 1 more Smart Citation
“…Ignjatovic et al . reported promising results from 40 women with 1 year follow up and demonstrated a favorable outcome at 1 year with post operative urodynamic studies showing unobstructed voiding in the majority 69 …”
Section: Newer Surgical Techniques For Suimentioning
confidence: 99%
“…Ignjatovic et al reported promising results from 40 women with 1 year follow up and demonstrated a favorable outcome at 1 year with post operative urodynamic studies showing unobstructed voiding in the majority. 69 Two methods of inserting a trans obturator tape are in existence and both involve the passage of a curved needle through the obturator foramen. The difference is in the direction of penetration.…”
Section: Trans Obturator Tape Insertionmentioning
confidence: 99%
“…There were high expectations and hopes because of the convenient pain profile, but the results were not as encouraging, and their use is performed with caution [22][23][24] . There are also self-tailored modifications or industrial modifications of the sling, which are applied with similar or equal success rates 25,26 .…”
Section: Mesh In the Treatment Of Stress Urinary Incontinencementioning
confidence: 99%